Monolithic zirconia crown does not increase the peri-implant strain under axial load - Tribst, Joao Paulo Mendes [UNESP]; Oliveira Dal Piva, Amanda Maria De [UNESP]; Riquieri, Hilton [UNESP]; Nishioka, Renato Sussumu [UNESP]; Bottino, Marco Antonio [UNESP]; Rodrigues, Vinicius Aneas (Wolters Kluwer Medknow Publications, 2019)
Aims: This study aimed to evaluate the influence of the crown type on the cervical microstrain around an external hexagon implant. Subjects and Methods: A dental manikin was impressed with addition-polymerizing silicone, and a hemiarch model was obtained with polyurethane resin. Then, a 3.75 mm x 11 mm implant was installed with 40 N/cm of torque in the region of element 36. Two groups were separated according to the type of crown used for rehabilitation: metal-ceramic crown (n = 10) or monolithic zirconia crown (n = 10). All crowns presented similar anatomy, with contact point in elements 35 and 37. Then, the polyurethane model was cleaned with isopropyl alcohol, and four strain gauges were bonded with cyanoacrylate adhesive in different areas (bucccal, lingual, mesial, and distal) around the implant. The crowns were installed with 20 N/cm torque, and an axial load (30 kgf) was applied in the center of the crown. Statistical Analysis: After performing 10 readings in each specimen, the data were analyzed by two-way analysis of variance and Tukey's test, all with alpha = 5%. Results: The results showed no statistical difference for the microstrain between the analyzed crowns (P = 0.065), and the microstrain values were different according to the area (P = 0.002): buccal (1514.9 +/- 233.8) > lingual (1280.8 +/- 245.5) > distal (373.2 +/- 105.2) > mesial (216.7 +/- 111.4). Conclusions: The crown type did not modify the microstrain in the peri-implant tissue.
Keywords: Dental implants; prosthetic dentistry; strain gauge